HUBUNGAN TINGKAT AKTIVITAS FISIK SEBELUM PERSALINAN DENGAN DURASI KALA II IBU PRIMIPARA DI FASILITAS KESEHATAN MALANG - Pamudita, Risca Rara; Indahwati, Lilik (Jurnal Ilmiah Bidan (JIB), 2024)
Maternal Mortality Rate (MMR) is one of the indicators to determine the quality of maternal health services in Indonesia. Obstetric complications are very influential on MMR, including second stage of labor. Physical activity that is carried out regularly can affect the increase in energy, straining power, his, breathing and flexibility of the birth canal so that it can affect the second stage of labor. However, mostly, women reduce physical activity when entering the third trimester of pregnancy. The research method used was observational analysis and cross-sectional approach conducted on 30 primipara mothers with physiological labor at the Malang Regional Health Facility. Rank-spearman statistical analysis was used to determine the meaningful relationship between variables. PPAQ questionnaires and partographs were used to collect research data. The level of physical activity of primipara mothers was categorized into sedentary levels as much as 4 respondents, the mild level is as much as 17 respondents and moderate levels as many as 9 respondents. This study shows that there is a significant relationship between the level of physical activity seven days before delivery and the duration of second stage in primipara mothers. The higher level of seven-day activity tends to shorten the duration of the second period of primipara's labor.